2010
DOI: 10.1128/jvi.01923-09
|View full text |Cite
|
Sign up to set email alerts
|

Highly Pathogenic H5N1 Avian Influenza Virus Induces Extracellular Ca 2+ Influx, Leading to Apoptosis in Avian Cells

Abstract: In this study, we show that the highly pathogenic H5N1 avian influenza virus (AIV) . Thus, we investigated the molecular mechanisms of apoptosis induced by H5N1-AIV infection. Caspase-dependent and -independent pathways contributed to the cytopathic effects. We further showed that, in the induction of apoptosis, the hemagglutinin of H5N1-AIV played a major role and its cleavage sequence was not critical. We also observed outer membrane permeabilization and loss of the transmembrane potential of the mitochondri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 64 publications
2
47
0
1
Order By: Relevance
“…Although the precise mechanism by which IAVs induce [Ca 2 þ ]i elevation remains obscure, the elimination of Ca 2 þ signalling by BAPTA-AM resulted in almost complete inhibition of virus internalization. In addition to this central role of Ca 2 þ in IAV infection, Ca 2 þ is also implicated in apoptosis of cells infected by a highly pathogenic H5N1 virus 50 , suggesting that the development of agents that target Ca 2 þ signalling might provide a new approach to the prevention and treatment of infection with a variety of influenza subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Although the precise mechanism by which IAVs induce [Ca 2 þ ]i elevation remains obscure, the elimination of Ca 2 þ signalling by BAPTA-AM resulted in almost complete inhibition of virus internalization. In addition to this central role of Ca 2 þ in IAV infection, Ca 2 þ is also implicated in apoptosis of cells infected by a highly pathogenic H5N1 virus 50 , suggesting that the development of agents that target Ca 2 þ signalling might provide a new approach to the prevention and treatment of infection with a variety of influenza subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…However, when [Ca 2ϩ ] i increases, stimulated AnxA6 is targeted to distinct subcellular membrane locations, such as the plasma membrane, endosomes, or secretory vesicles. Thus, cytosolic AnxA6 is probably translocated to distinct subcellular membrane locations upon virus infection, due to the dysregulation of Ca 2ϩ homeostasis observed after IAV infection (24,58). If AnxA6 is overexpressed and targeted at the plasma membrane, it has been shown that it interacts with, recruits, and causes the rearrangement of F-actin, resulting in stabilization of the cortical cytoskeleton (40).…”
Section: Discussionmentioning
confidence: 99%
“…However, upon apoptosis induction, nuclear translocation of AIFM1 occurs via a caspaseindependent pathway. This pathway has recently been shown to be activated by influenza virus (H5N1), leading to mitochondrial dysfunction and cell death through the induction of an extracellular Ca2 ϩ influx (62). However, the viral component involved in the activation of this caspase-independent pathway is unknown.…”
Section: Vol 85 2011mentioning
confidence: 99%